Factors Influencing Fraud in Educational Institutions: The Moderating Role of Personal Integrity - Noor Abidin, Fityan Izza; Biduri, Sarwenda; Gunawan, Giezka Adinia; Putri, Vanesya Ardiana (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2026)
Purpose: The purpose of this research is to analyze the influence of a sense of financial accountability, religiosity, and morality on fraud in educational institutions, with personal integrity as a moderating variable. Previous research has shown inconsistent results regarding the influence of a sense of financial accountability, religiosity, and morality on fraud; therefore, personal integrity was used as a moderating variable because it can determine an individual’s consistency in applying moral values and honesty, thereby helping to explain the differences in previous research findings. Methodology/approach: This research uses a quantitative approach based on primary data obtained through the distribution of questionnaires to teachers, financial directors, treasurers, and school administrators at Amal Usaha Muhammadiyah Pendidikan Sepanjang, with a total of 36 respondents. Data analysis was conducted using Partial Least Squares (PLS) with the assistance of SmartPLS. Findings: The results indicate that a sense of financial accountability and religiosity have a positive and significant effect on fraud prevention. Conversely, morality does not have a significant effect on fraud. Personal integrity was found to act as a partial moderator, with only one interaction showing a significant effect. Practical implications: This research emphasizes that educational institutions need to strengthen their oversight systems and culture of accountability in order to minimize the potential for fraud within these institutions. Originality/value: This research contributes to the development of a fraud prevention model for educational institutions based on individual values by positioning personal integrity as a factor that reinforces the relationship between accountability, religiosity, and fraud in educational institutions.